1998
DOI: 10.1523/jneurosci.18-09-03186.1998
|View full text |Cite
|
Sign up to set email alerts
|

Type I Adenylyl Cyclase Mutant Mice Have Impaired Mossy Fiber Long-Term Potentiation

Abstract: Long-term potentiation (LTP) at the mossy fiber-->CA3 pyramidal cell synapse in the hippocampus is an NMDA-independent form of LTP that requires cAMP-dependent protein kinase (PKA) activity and can be induced by forskolin, a general activator of adenylyl cyclases. Presynaptic Ca2+ influx and elevated cAMP may be obligatory for mossy fiber LTP. Because the Ca2+-stimulated type 1 adenylyl cyclase (AC1) is expressed in the dentate gyrus and CA3 pyramidal cells, it is hypothesized that AC1 may be critical for moss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
145
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(157 citation statements)
references
References 68 publications
10
145
1
1
Order By: Relevance
“…They found that Rab3A knockout mice present no detectable defect in learning and memory. These data indicate that deficient mossy fiber LTP is probably not the reason for the spatial learning defect of RIM1-alpha mutants, in agreement with other studies in mutant mice lacking Rab3A 169 or with defects in PKA activity Huang et al; 170 see also Villacres et al, 171 Wu et al 172 and Otto et al 173 In order to investigate whether the decrease in Pr could be the cause of the behavioral phenotype, Powell et al included in the analysis synaptotagmin 1 R233Q knockin mice to compare them with RIM1-alpha mutants. Synaptotagmin 1 is a Ca 2 þ sensor for fast and synchronous exocytosis.…”
Section: Rim1-alpha Is Critical For Learning and Memorysupporting
confidence: 90%
“…They found that Rab3A knockout mice present no detectable defect in learning and memory. These data indicate that deficient mossy fiber LTP is probably not the reason for the spatial learning defect of RIM1-alpha mutants, in agreement with other studies in mutant mice lacking Rab3A 169 or with defects in PKA activity Huang et al; 170 see also Villacres et al, 171 Wu et al 172 and Otto et al 173 In order to investigate whether the decrease in Pr could be the cause of the behavioral phenotype, Powell et al included in the analysis synaptotagmin 1 R233Q knockin mice to compare them with RIM1-alpha mutants. Synaptotagmin 1 is a Ca 2 þ sensor for fast and synchronous exocytosis.…”
Section: Rim1-alpha Is Critical For Learning and Memorysupporting
confidence: 90%
“…We found that modulation of cAMP signaling indeed influenced the percentage of presynaptically active synapses, con-sistent with a cAMP "tone" maintaining basal activation status of glutamate terminals. To test whether Ca 2ϩ -dependent isoforms of adenylyl cyclase (AC) are involved in maintaining activation status of terminals, we examined synapses from mice deficient in AC1 and AC8, which have been implicated previously in synaptic plasticity (Villacres et al, 1998;Wong et al, 1999;Wang et al, 2003;Gong et al, 2007). We found that AC1 and AC8 were not necessary for maintaining a strong majority of active synapses.…”
Section: Introductionmentioning
confidence: 99%
“…Only the initial phase and D-LTP were affected. In the CA3 region of the hippocampus, the Mossy fiber LTP require both type-1 and type-8 adenylyl cyclases (Villacres et al 1998;Victor Pineda and Daniel Storm, unpublished data). Our data, coupled with the electrophysiology studies suggest that different spatial localization of AC1 may lead to different strength of cAMP signaling.…”
Section: Discussionmentioning
confidence: 98%
“…Although the late phase of long-term potentiation (L-LTP) of the postsynaptic NMDA receptor-dependent Schaffer collateral/CA1 pathway was intact in the mutant mice, the initial phase was affected (Wu et al 1995;Wong et al 1999). On the other hand, studies using AC1 mutant mice demonstrated that AC1 is crucial for mossy fiber/CA3 and cerebellar parallel fiber synapse LTP Villacres et al 1998). These two forms of LTPs depend on presynaptic components, rather than postsynaptic NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation